From Dysfunction to Functionalism: the Evolution of Military Construction in The Interwar Period Poland - Rudnicka-Bogusz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article is the general characteristics of military residential architecture built in the 1920s and 1930s in the 2nd Polish Republic. In the newly restored Poland the most pressing problem was the improvement of the housing conditions of the population. The military, who contributed the most to the reinstating of independence held special privilege with the state officials. Therefore, the problem of their quartering was resolved with utmost preference.
Keywords: modernist architecture; Military Accommodations Fund; military housing; improvement housing conditions; architektura modernistyczna; Fundusz Kwaterunku Wojskowego; mieszkania wojskowe; poprawa warunków mieszkaniowych